(untitled) (Resunga Journal रेसुङ्गा जर्नल, 2023)
This paper focuses on the preliminary processes of conducting a research work. Its target readers are those students who are new to research area. Given this fact, the fundamental objective of this paper is to familiarize them with the basic definitions and important elements of research. This article collects insights by employing two methods. First, it draws upon the experience of its author as a teacher and researcher. This personal resource renders the article reflective and employs the personal pronoun I. Second, it resorts to documents pertinent to research and academic writings. The paper assigns no separate section for reviewing the past works. Instead, to aid smooth transition and readership, they have been invoked and interlarded in the main body during the discussion. Because the intended readers of this paper are neophytes, simplified version of research terminologies has been used for easy comprehension.